Profitability, Leverage, and Institutional Ownership in Explaining Reporting Timeliness - Amor, Atika; Ayuni Lailatul Addha (Hikamatzu | Journal of Multidisciplinary, 2025)
This study investigates the effect of profitability, leverage, and institutional ownership on the timeliness of financial reporting in property and real estate companies listed on the Indonesia Stock Exchange during the 2021–2023 period. Using a quantitative approach with logistic regression analysis, the study employs purposive sampling on 34 companies. The results reveal that none of the three variables significantly influence the timeliness of financial reporting, either partially or simultaneously. These findings suggest that other factors beyond financial indicators might play a more decisive role in timely financial reporting.